(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
Whilst there has been substantial growth in brief therapies in recent years there have been limited attempts to specifically theorise the practice of brief existential therapy. Moreover, the recent attempts to provide guidelines for brief existential practice (Strasser and Strasser, 1997) provide only limited advances on ’traditional’ open-ended existential practice. In this paper, I seek to explore the possibility of employing techniques from solution focussed therapy (SFT) in brief existential practice. I argue that the relatively a-theoretical nature of SFT readily enables the existential practitioner to engage with these techniques and indeed provide the necessary theoretical ground for this particular form of practice. Whilst making the case for the use of SFT in brief existential practice I also aim to highlight the possible difficulties of such a move and the tensions that might emerge from integration.